1997
DOI: 10.1111/j.1834-7819.1997.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐antral temporalis transfer for the repair of adult cleft palates

Abstract: Temporalis muscle transfer is a versatile technique frequently used for reconstructive procedures in the maxillofacial region. However the thickness of the pedicle may interfere with masticatory function when used anteriorly in the oral cavity. To repair fulllength mid-palatal defects in fully dentate patients the flap can be passed through the maxillary sinus and combined with local repair of the soft palate, thus avoiding any occlusal trauma from the posterior teeth. The operation is a single stage procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…But, we could not do surgery at time, as patients were malnourished. The male female ratio (1.5:1) in our study group was similar (1.5:1 to 2.1:1) with other 3,7,14 . Side of cleft is also similar to the literatures where showed more cleft involvement in the left side than the right.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…But, we could not do surgery at time, as patients were malnourished. The male female ratio (1.5:1) in our study group was similar (1.5:1 to 2.1:1) with other 3,7,14 . Side of cleft is also similar to the literatures where showed more cleft involvement in the left side than the right.…”
Section: Discussionsupporting
confidence: 49%
“…Even after surgery, they may present with wound disruption or recurrent oronasal fistula formation. Some parents prefer cleft lip repair first irrespective of the age of the child, only for esthetic reasons, and do not come again for cleft palate or oronasal fistula closure 3 . Palatoplasty often needs extensive dissection, specially if the age of the patients is more and there may be more chances of oronasal fistula formation, which is very difficult to repair, and may cause mid-facial growth disturbance 7,12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study John F arvier showed that for the repair of the adult cleft palate the transantral transfer of TMF is a single stage procedure with low morbidity and few complication. 4 The present study was designed to find out the efficacy of temporalis myofascial flap for reconstruction of various defects of maxillofacial region after tumour surgery in the department of Oral and Maxillofacial Surgery (OMS), Dhaka Dental College & Hospital (DDCH).…”
Section: Introductionmentioning
confidence: 99%